Phase I trial of valaciclovir, the L-valyl ester of acyclovir, in patients with advanced human immunodeficiency virus disease. - Jacobson, M A (1994)
Valaciclovir, the L-valyl ester of acyclovir, is rapidly and extensively converted in humans to acyclovir after oral administration by first-pass metabolism. A phase I study was conducted in two cohorts of volunteers with advanced human immunodeficiency virus (HIV) disease (absolute CD4 lymphocyte count of < 150 cells per microliters) who received oral valaciclovir at dosages of 1,000 or 2,000 mg four times daily for 30 days. All patients were clinically stable without any changes in underlying HIV-related medications for > or = 6 weeks prior to entry in study; these medications were continued throughout the study. Multiple-dose administration of valaciclovir showed a generally favorable safety profile. Nausea, vomiting, diarrhea, and abdominal pain each were reported in < or = 31% of the patients; of these symptoms, only one episode of diarrhea was considered causally related to valaciclovir exposure. Four patients developed neutropenia (two at each dose level) which was not clinically significant. There were no renal or neurologic adverse events. Valaciclovir was rapidly absorbed and converted to acyclovir, with plasma valaciclovir levels generally undetectable or levels of < or = 0.4 microgram/ml. After 3 h postdosing, valaciclovir was not detectable in plasma. Acyclovir was measurable in plasma as early as 15 min following valaciclovir dosing, and plasma concentrations of acyclovir greatly exceeded those of valaciclovir. The mean values for the maximum concentration of drug in plasma, time to maximum concentration of drug in plasma, area under the concentration-time curve from 0 h to infinity, and apparent half-life of acyclovir obtained after single- and multiple-dose valaciclovir administration in HIV-infected patients were similar to those reported in normal healthy volunteers. The time to maximum concentration in serum and half-life of acyclovir after valaciclovir administration were approximately 2 and 3 h, respectively, which were similar to those reported after oral administration of acyclovir itself. The mean trough and peak acyclovir concentrations and the daily area under the concentration-time curve acyclovir values at steady state were 2.5 and 8.4 micrograms/ml and 120 h micrograms/ml, respectively, after a dosage of 2,000 mg of valaciclovir four times daily. These values were approximately fivefold greater than those achieved with high dosages of oral acyclovir (800 mg, five times daily) and were not affected by continued use of medications necessary for management of advanced HIV disease. Thus, 2,000 mg of valaciclovir given orally four times daily should be evaluated for its potential efficacy in suppressing cytomegalovirus and other herpes group virus infections not optimally managed with current oral acyclovir therapy.